Discharge in a high-pressure gas, initiated by a beam of fast electrons; Journal of Applied Mechanics and Technical Physics; Vol. 12, № 6 - Koval'chuk B. M.; Kremnev V. V.; Mesyats G. A. Gennady Andreyevich; Potalitsyn Yu. F. (1971, 1971)
В фонде НТБ ТПУ отсутствует